Perinatal maternal characteristics predict a high risk of neonatal asphyxia: A multi-center retrospective cohort study in China - Yu, Yi; Gao, Jinsong; Liu, Juntao; Tang, Yabing; Zhong, Mei; He, Jing; Liao, Shixiu; Wang, Xietong; Liu, Xinghui; Cao, Yinli; Liu, Caixia; Sun, Jingxia (Frontiers in Medicine, 2022)
Objective: This study aimed to identify various perinatal maternal characteristics that contributed to neonatal asphyxia(NA) in term and late-preterm newborns based on the data obtained from a Chinese birth registry cohort and to establish an effective model for predicting a high risk of asphyxia. Method: We retrospectively reviewed and analyzed the birth database from July 1, 2016, to June 30, 2017, in the main economically developed regions of China. Asphyxia was defined as an Apgar score <7 at 5 min post-delivery with umbilical cord arterial blood pH<7.2 in the infant born after 34weeks. We compared the perinatal maternal characteristics of the newborns who developed asphyxia(NA group, n=1,152) and those who did not(no NA group, n=86,393). Candidate predictors of NA were analyzed using multivariable logistic regression. Subsequently, a prediction model was developed and validated by an independent test group. Result: Of the maternal characteristics, duration of PROM≥48hr, a gestational week at birth<37, prolonged duration of labor, hypertensive disorder, nuchal cord, and birth weight<2500 or ≥4000g, abnormal fetal heart rate, meconium-stained amniotic fluid, and placenta previa were included in the predicting model, which presented a good performance in external validation(c-statistic of 0.731). Conclusion: Our model relied heavily on clinical predictors that may be determined before or during birth, and pregnant women at high risk of NA might be recognized earlier in pregnancy and childbirth using this methodology, allowing them to avoid being neglected and delayed. Future studies should be conducted to assess its usefulness.